2020
DOI: 10.1186/s40795-020-00371-6
|View full text |Cite
|
Sign up to set email alerts
|

What factors are associated with the increase of anemia in Ethiopian children aged 6 to 59 months between 2011 and 2016?

Abstract: Background In Ethiopia more than half of the children under 5 years are anemic and between 2011 and 2016 anemia in children under-5 increased by 28.7%. This study aimed to analyze this increase in anemia by socio-demographic characteristics. Method This study was a secondary analysis of the data from the Ethiopian Demographic Health Surveys (EDHS) for 2011 and 2016. The increase of anemia was calculated using percentage change. The chi-square test was used to determine the association between anemia and six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…2 According to the Ethiopian Demographic and Health Survey (EDHS) of 2016, 38% of children less than 5 years of age were stunted and 57% were anaemic. 3 When looking only at the age group of 2-5 years, the recent study in Ethiopia reported 33% of prevalence for anaemia 4 and 45% of prevalence for stunting. 5 Both anaemia and stunting during early life can lead to serious health effects later in life such as increased susceptibility to infections and chronic diseases, impaired cognitive and physical development, and low economic productivity of individuals and the society.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 According to the Ethiopian Demographic and Health Survey (EDHS) of 2016, 38% of children less than 5 years of age were stunted and 57% were anaemic. 3 When looking only at the age group of 2-5 years, the recent study in Ethiopia reported 33% of prevalence for anaemia 4 and 45% of prevalence for stunting. 5 Both anaemia and stunting during early life can lead to serious health effects later in life such as increased susceptibility to infections and chronic diseases, impaired cognitive and physical development, and low economic productivity of individuals and the society.…”
Section: Introductionmentioning
confidence: 99%
“…2 According to the Ethiopian Demographic and Health Survey (EDHS) of 2016, 38% of children less than 5 years of age were stunted and 57% were anaemic. 3 When looking only at the age group of 2–5 years, the recent study in Ethiopia reported 33% of prevalence for anaemia 4 and 45% of prevalence for stunting. 5 …”
Section: Introductionmentioning
confidence: 99%
“…For instance, the prevalence of anaemia increased sharply from 44 to 57% among children aged 6–59 months in Ethiopia between 2011 to 2016 [ 9 ]. The cause of this recent increments in childhood anaemia is not well-defined [ 14 ] and this sharp increase of anaemia may be due to selection bias. Furthermore, the Ethiopian National Nutrition Program's (NPP) second phase (2015–2020) failed to reduce anaemia in children aged 6–59 months from 39 to 24% by 2020, necessitating a recalculation of the national strategy [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies in Ethiopia on anaemia were mainly localised [ 23 27 ], and the population-based studies on anaemia have focused on the prevalence and socio-demographic determinants [ 5 , 14 , 28 30 ]. Additional studies have mapped anaemia distribution [ 28 , 31 , 32 ] and regional inequalities [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…stunting, wasting, and underweight) as a potential mechanism. Previous studies investigated different forms of child undernutrition [ 45 52 ] and anemia [ 53 57 ] in Ethiopia, however, information regarding the association of OD with anemia is limited. Given the limited evidence on the relationship between OD and child anemia, the objective of this study was twofold: [ 1 ] to investigate the association between OD and anemia in children 6–59 months of age in Ethiopia, and [ 2 ] to examine whether childhood undernutrition (i.e.…”
Section: Introductionmentioning
confidence: 99%